Abstain Voter (Golput) On Implementation Simultaneous Regional Head Elections (Pilkada) In Surabaya During The Corona Pandemic - andy christanto santoso; Woro Winandi (Faculty of Law, Merdeka University Surabaya, Indonesia, 2022)
The implementation of simultaneous regional head elections (Pilkada) during the Covid-19 Pandemic was faced by the people of Indonesia in 2020. The East Jave government especially issued several regulations where all of these regulations have the same purpose, namely limiting social interactions or it can be called PSBB vol. 1, PSBB volume 2, PSBB volume 3. on December 9, 2020, Indonesia will carry out the Pilkada. From the past Pilkada experience, the number of people interested in casting their votes has decreased over time. Based on the spirit or mother of all laws in Indonesia. Does it reflect social justice for all Indonesian people? What innovations should the government make during this pandemic so that there is no clash between regulations issued during this pandemic?